2004
DOI: 10.1128/aem.70.6.3733-3735.2004
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Enhanced Culture Recovery of Francisella tularensis

Abstract: Francisella tularensis is found in a wide variety of hosts and extrahost environments, making culture recovery a diagnostic challenge. Here we demonstrate improved recovery times and good sensitivity (90%) when cultures were inoculated on the site of an investigation using fresh tissues. For contaminated specimens, antibiotic supplementation of enriched cysteine heart agar blood culture medium improved recovery of F. tularensis by 81.1%. For transport of tissues, immediate freezing yielded culture recovery rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 8 publications
0
57
0
Order By: Relevance
“…Evidence suggests that some bacteria inhibit F. tularensis growth [57]. This finding has important implications when attempting to isolate F. tularensis from a variety of samples that contain other bacterial species.…”
Section: Culturementioning
confidence: 96%
See 1 more Smart Citation
“…Evidence suggests that some bacteria inhibit F. tularensis growth [57]. This finding has important implications when attempting to isolate F. tularensis from a variety of samples that contain other bacterial species.…”
Section: Culturementioning
confidence: 96%
“…This finding has important implications when attempting to isolate F. tularensis from a variety of samples that contain other bacterial species. Recently, an antibiotic supplemented CHAB media (CHAB-A) was shown to significantly improve recovery rates of F. tularensis from tissue sources contaminated or overgrown by other flora [57]. In clinical or environmental specimens where mixed flora is likely, the use of CHAB-A should be considered.…”
Section: Culturementioning
confidence: 99%
“…Numbers of CFUs in organs from infected mice were determined as previously described (9), using groups of three to five mice. CFUs in lungs of infected mice were assessed by plating organ homogenates on MHA plates containing an antibiotic mixture to suppress growth of adventitious agents (colistin sulfate salt, lincomycin hydrochloride, trimethoprim, and ampicillin) (11).…”
Section: Animals Infections and Determination Of Bacterial Organ Bumentioning
confidence: 99%
“…It is possible that the yield of cultures is improved by bedside or rapid inoculation into broth or culture plates since there is often a delay between the acquisition of a sample and its arrival at the microbiology laboratory. An improved yield was observed by rapid plate inoculation of necropsy samples from infected prairie dogs [37]. In addition, this study reported that utilizing media with antibiotics also improved the yield of cultures.…”
Section: Culturementioning
confidence: 60%